From Mass to Personalized Mobile Marketing Strategies: The New Dimensions Through Expert Systems - Barutcu, Suleyman; Yaldir, Abdulkadir; Hasiloglu, Selcuk Burak (European Scientific Journal, ESJ, 2017)
Today, mass mobile marketing and advertising are beginning to lose their positions and personalized (individualized) mobile marketing has started to dominate as a new way of marketing strategy, because expert systems, as a subsection of artificial intelligence, are able to help sending personalized messages to thousands of customers taking into their differences in a very short time. Expert systems provide marketers to serve customers efficiently and individually, and integrate customer characteristics, locations, data and rules to send personalized messages like a marketer. With expert system-based personalized mobile marketing, mobile phone users will receive personal and location specific mobile marketing messages with great benefits. Providing personalized information to marketers with expert systems will send more appropriate messages, create better customer satisfaction and increase mobile marketing efficiency by targeting the right consumers. Therefore, personalized mobile marketing has the potential of becoming a major mechanism in the future of mobile marketing. The objectives of this study are to draw marketers and entrepreneurs’ attention to expert system-based personalized mobile marketing and develop a draft expert system to send personalized mobile marketing messages to targeted customers. At the end of this study, some recommendations to expert system developers and a draft expert systembased personalized mobile marketing application are given.